1982
DOI: 10.3102/00346543052001007
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Context of Individual Efficacy

Abstract: Efficacy-the individuaΓs perceived expectancy of obtaining valued outcomes through personal effort-appears to yield a variety of important effects in school organizations. Efficacy has been identified as a social psychological antecedent to many individual-level outcomes, such as student performance and teacher effectiveness. Program implementation and evaluation studies also increasingly point to efficacy as a significant determinant of resistance to, or persistence of organizational interventions. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 35 publications
4
19
1
1
Order By: Relevance
“…The creation of study groups for staff development addressed the conceptual factors regarding mandated tasks and resource exchange and relevancy (Fuller et al, 1982;Hoy & Woolfolk, 1993). By organizing staff development around teachers' own beliefs, the process allowed teachers to play a primary role in the implementation of the district's mandated tasks.…”
Section: Duringmentioning
confidence: 99%
“…The creation of study groups for staff development addressed the conceptual factors regarding mandated tasks and resource exchange and relevancy (Fuller et al, 1982;Hoy & Woolfolk, 1993). By organizing staff development around teachers' own beliefs, the process allowed teachers to play a primary role in the implementation of the district's mandated tasks.…”
Section: Duringmentioning
confidence: 99%
“…Notably, when considering the association between organizational climate and personal factors, it has been suggested that organizational conditions can enhance or diminish teachers’ personal resources. For example, the Fuller framework (1982) suggests that teachers’ efficacy is improved by structural conditions such as caring relations among teachers as well as feeling supported by administrators (Fuller, Wood, Rapoport, & Dornbusch, 1982; Hoy & Woolfolk, 1993). Similarly, burnout, another important personal resource, promotes disengagement as demonstrated by the job demands-resources model, which describes how exhaustion and disengagement from work can result from stressful job demands and a lack of external and internal resources (e.g., supervisor support, colleague support; Demerouti, Bakker, Nachreiner, & Schaufeli, 2001).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Examining the role of teachers’ perceptions of a school’s organizational climate is also necessary in understanding teacher resources as well as openness to adopting new practices (Aarons, 2005; Aarons et al, 2014; Fuller et al, 1982). Principals are curriculum “gatekeepers” and set priorities for the school and thus likely impact teachers’ attitudes towards new practices (Hallinger & Heck, 1996; Han & Weiss, 2005).…”
Section: The Role Of School Organizational Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Important antecedents of teacher efficacy have included teacher training and experience (Hoy and Woolfolk, 1993;Ramey-Gassert et al, 1996), the academic ability of one's students (Smylie, 1988), and school and community support (Fuller et al, 1982;Hoy and Woolfolk, 1993;Park, 1992;RameyGassert et al, 1996).…”
Section: Introductionmentioning
confidence: 99%